Keefektifan Media Pop Up Book terhadap Kemampuan Membaca dan Menulis Siswa Tunagrahita Ringan di SLB - Amelia Rizky Idhartono (Neolectura, 2020)
This research intends to see the effectiveness of pop-up book media to the ability to read and write to the child. This type of research uses single subject research (SSR) where the criteria in this experimental study used A-B-A design. The study was used to examine one or more subjects to determine the influence gained after some treatment with the media already created. The subject in this study is a V-grade student at Widya Shantika District of Malang. Based on the results of Test t that has been done, it can be stated that the product development of prototype media pop-up book effective to improve the ability to read and write understanding Shiva Light class V SDLB. This effectiveness is expressed with the result of the value obtained, namely: T = 53.105 > 2.105 then H º rejected and H ¹ received so that the claim is accepted. Pop-up book media is precisely used as a learning medium for students who have the physical composition and the content of the book is very appealing to students. Interest in the pop-up book is able to increase students ' interest in learning the material inside. When students have studied the material continually with euphoric feelings and high spirits, the result of assessment of learning will increase.